Tanya M. Tarbutton & Lori B. Doyle 233 Assessment of Distance Learning Practices during the COVID-19 Pandemic in Grades K-12 - Ebru Turan-Güntepe; Tuğçe Durmuş; Necla Dönmez-Usta (Athens Institute for Education and Research, 2023)
This study aims to examine the distance learning practices carried out at the primary education level during the COVID-19 pandemic from students' and their parents' perspectives. The study was conducted with 76 primary school students at different grade levels, including their parents (76), in the state schools of Giresun city in the spring semester of the 2019-2020 academic year. The study was based on the case study method, one of the qualitative research designs. An information collection form with open-ended questions was used as a data collection tool. The data obtained from the information collection form were analyzed by the content analysis method. The findings have revealed that the distance learning system has a flexible structure and is accessible from any place, but there are difficulties accessing the system due to connection problems. These systems facilitate the teaching process, affecting learning positively. The findings also showed that distance learning systems are not favored by students who long for friends and teachers during the learning process performed on these systems. Unlike face-to-face training, disciplinary and supervision problems in distance learning are also noteworthy. The authors finally suggest that the distance learning and management process should be performed in a restrained manner to ensure the process to be run effectively and efficiently